The Latin American Brain Health Institute, a regional initiative to reduce the scale and impact of dementia. Issue 9 (16th June 2022) - Duran‐Aniotz, Claudia; Sanhueza, Jorge; Grinberg, Lea T.; Slachevsky, Andrea; Valcour, Victor; Robertson, Ian; Lawlor, Brian; Miller, Bruce; Ibáñez, Agustín
Abstract: Latin American and Caribbean countries face complex challenges to improve brain health and reduce the impact of dementia. Regional hubs devoted to research, capacity building, implementation science, and education are critically needed. The Latin American Brain Health Institute represent an important step to address many of these needs.